Challenges and Conservation: Parrot Inventories in the Heart of the Congo Basin - Ntiendjui, Levis Gapessie; Tamungang, Simon Awafor; Piebeng, Ghislain Noé Kougoum; Ateufack, Gilbert; Wabo, Josué Pone; Ngouateu, Omer Bébé; Tchoumboue, Joseph (Innovations in Biological Science Vol. 4, 2024)
The aim of this study is to contribute to better management of the avian fauna in the Congo Basin, and in particular in the greater Mbam area of Cameroon. Biodiversity is the wealth constituted by all forms of life on earth. It can be considered at three interdependent levels: genetic, specific and ecosystemic. To inventory parrots, determine their relationship with vegetation and the threats they face, 10 transects in parallel lines measuring 2 km long and spaced 30 km apart were randomly selected in the study area (4°10 - 5°20 N; 10°30 - 11°50 E), consisting of the Mbam and Inoubou site, which is predominantly savannah, and the Mbam and Kim site, which is predominantly forest. The transects were walked simultaneously on 02 / 02 / 2011 (dry season) between 6.30 a.m and 8.30 a.m, then on 20 / 08 / 2011 (rainy season) at the same time, by 10 teams of 3 people equipped with binoculars. 500 people were interviewed to obtain additional information on the parrots' activities and uses. In the rainy season, Grey Red-tailed Parrots (GRTP) identified in the forests and savannahs of the Mbam and Inoubou site with a relative abundance (RA) of 3.97x103 and in the forests of the Mbam and Kim site (RA = 5.00x103), are less numerous than Red-headed Lovebirds (RHL) observed only in the savannahs of the Mbam and Inoubou site (RA = 1.94x104), and more abundant than Senegal Green Parrots (SGP) which colonise both the forests and savannahs of the Mbam and Kim site (RA = 3.78x103). All these parrots (AR = 3.21x104) migrate during the dry season. The absence of parrots in the study area during the long dry season is due to the fact that the food resources available are insufficient in quantity and nutritional quality to maintain their populations during this arid period, forcing them to migrate in order to survive. The parrots use 26 plant species belonging to 20 families. The Mbam and Inoubou site uses a higher biodiversity of plants. In the Mbam et Kim site, Melicia excelsa and Terminalia superba are heavily utilized by GRTP and SGP for perching, roosting, and breeding. However, at the same time, logging is heavily deforesting these species, endangering their habitats. Poaching is another hazard to the GRTP.